2009 Agile Conference 2009
DOI: 10.1109/agile.2009.70
|View full text |Cite
|
Sign up to set email alerts
|

The XP Customer Team: A Grounded Theory

Abstract: The initial definition of XP resulted interpreting the on-site customer to be We have conducted extensive quali studying XP teams, and one of our res was "who is the customer"? We fou than a single person, a customer team a this paper we outline the different r typically on the team, which range from "Acceptance Tester" role to the less r of "Political Advisor" and "Super-Secr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…Three XP customer functions have been identified that address collaboration within teams: geek interpreter, political advisor and technical liaison (Martin et al, 2009b). A geek interpreter improves communication between technical team members and the business.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three XP customer functions have been identified that address collaboration within teams: geek interpreter, political advisor and technical liaison (Martin et al, 2009b). A geek interpreter improves communication between technical team members and the business.…”
Section: Discussionmentioning
confidence: 99%
“…Technical liaison coordinates with other related projects and technical specialist groups residing within the organisation. The three collaboration functions exist alongside four direction setting roles: negotiator, diplomat, supersecretary and customer coach (Martin et al, 2009b). The negotiator gains agreement from stakeholders on a single vision for the software under development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GT was originally developed by Barney G. Glaser and Anslem L. Strauss [32]. GT is successfully being used to study the social nature of Agile teams [25,40,47,58,69]. We chose GT as our research method for two main reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, GT allows researchers to study social interactions and the behaviour of people in the context of solving problems, and Agile methods focus on people and their interactions in software development teams [16]. Notably, GT is increasingly being used successfully to study the social nature of Agile teams [29,30,31,32,33].…”
Section: Grounded Theorymentioning
confidence: 99%